Synthesis and characterization of some new novel pyrazoline and thiazepine derivatives from chalcones. (Journal of the College of Basic Education, 2023)
A bis-chalcones(1,2)in scheme 1 were prepared by the reaction of terephthaldehyde with acetophenone to give compound(1) or P-bromo acetophenone to give compound(2) in alkaline medium. treatment of this chalcones with hydrazine hydrate /phenylhydrazine/ semicarbazide hydrochloride / thiosemicarbazide afforded bis-pyrazoline derivatives but treatment chalcones (1,2) with cysteine(amino acid) gave (4E,4'E)-7,7'-(1,4-phenylene)bis(5-phenyl-2,3,6,7-tetrahydro-1,4-thiazepine-3-carboxylic acid) (11,12) in good yields. All new compounds have been characterized by their melting points, FT.IR, H,NMR, 13C-NMR spectra and checked by TLC.